Administrative Efficiency of The Village Program Shines in The City of Semarang - Anita Febriana; Yuniningsih, Tri; Putranti, Ika Riswanti (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The Drug-Free Village Program (Desa Bersinar) is a strategic initiative by the Indonesian government aimed at eradicating drug abuse at the village level. The program's urgency is heightened in large cities like Semarang, which face complex social and cultural diversity. Administrative efficiency is critical to ensuring optimal resource utilization and achieving the program’s objectives. This study aims to analyze the level of administrative efficiency in the Desa Bersinar program in Semarang City and identify influencing factors. This research employs a quantitative descriptive approach, utilizing questionnaires distributed to village officials involved in program implementation and in-depth interviews with key informants. Quantitative data were analyzed using descriptive statistics, while qualitative data were thematically analyzed. The findings reveal that the program demonstrates good administrative efficiency, yet challenges remain, including the limited competence of village officials and bureaucratic inefficiencies. The use of information technology has shown potential in expediting administrative processes but has not been fully optimized. The novelty of this study lies in its combined use of quantitative and qualitative analyses to provide a comprehensive overview of administrative efficiency in a village-level drug prevention program. Key recommendations include enhancing human resource capacity, strengthening the integration of information technology, and increasing the frequency and quality of program evaluations. These findings offer valuable insights for improving the program's implementation and serve as a reference for similar initiatives in other regions.